Electro-mechanical properties of triblock copolymer styrene-butadiene-styrene / carbon nanotube composites for large deformation sensor applications - Costa, P. (2013)
Thermoplastic elastomer/carbon nanotube composites are studied for sensor applications due to their excellent mechanical and electrical properties. Piezoresisitive properties of tri-block copolymer styrene-butadiene-styrene (SBS)/ carbon nanotubes (CNT) prepared by solution casting have been investigated. The initial elastic modulus of the SBS/CNT composites increases with increasing the CNT filler content present in the samples, without losing the high deformation capability of the polymer matrix (~1500 %). Furthermore, above the percolation threshold these materials are unique for the development of large deformation sensors due to the strong piezoresistive response. Piezoresistive properties evaluated by uniaxial stretching in tensile mode and 4-point bending showed Gauge Factors up to 120. The linearity obtained between strain and electrical resistance makes these composites interesting for large strain piezoresistive sensors applications.